2005
DOI: 10.1124/jpet.104.076869
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Effects of Prucalopride, a Novel Enterokinetic Agent, on Isolated Atrial Myocytes from Patients Treated with β-Adrenoceptor Antagonists

Abstract: Prucalopride is a selective 5-hydroxytryptamine type 4 (5-HT 4 ) receptor agonist developed for the treatment of gastrointestinal disorders. The endogenous agonist 5-HT acting via 5-HT 4 receptors increases the L-type Ca 2ϩ current

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…Previous lines of evidence have shown that 5-HT and prucalopride increase the L-type calcium current (I [ca] ) in human isolated atrial myocytes (Pau et al, 2003(Pau et al, , 2005. Accordingly, we have now shown in human atrial trabeculae that 5-HT and 5-MeOT induced contractile responses were attenuated by verapamil (about 40%).…”
Section: Role Of Calcium Channels In the Positive Inotropic Responsesmentioning
confidence: 76%
“…Previous lines of evidence have shown that 5-HT and prucalopride increase the L-type calcium current (I [ca] ) in human isolated atrial myocytes (Pau et al, 2003(Pau et al, , 2005. Accordingly, we have now shown in human atrial trabeculae that 5-HT and 5-MeOT induced contractile responses were attenuated by verapamil (about 40%).…”
Section: Role Of Calcium Channels In the Positive Inotropic Responsesmentioning
confidence: 76%
“…In human atrial myocytes and only at doses that were markedly supratherapeutic, prucalopride acted as a partial agonist of L-type calcium channels. 35 However, there were no effects on late repolarizations or the refractory period and there was no evidence of any arrhythmic activity. 35 Prucalopride: clinical evidence in chronic idiopathic constipation Based on the aforementioned effects of prucalopride on colonic motility and transit, [30][31][32] it should come as no surprise that a major clinical focus has been on its therapeutic role in constipation.…”
Section: -Ht4 Receptor Agonists In CCmentioning
confidence: 94%
“…35 However, there were no effects on late repolarizations or the refractory period and there was no evidence of any arrhythmic activity. 35 Prucalopride: clinical evidence in chronic idiopathic constipation Based on the aforementioned effects of prucalopride on colonic motility and transit, [30][31][32] it should come as no surprise that a major clinical focus has been on its therapeutic role in constipation. Efficacy, tolerability, safety and impact on quality of life have been demonstrated in a number of large, randomized, placebo-controlled trials 36 which have led to the approval of prucalopride in several countries, with the usual recommended dose being 2 mg per day in patients under 65 years of age and 1 mg per day in patients over 65 years.…”
Section: -Ht4 Receptor Agonists In CCmentioning
confidence: 94%
“…Interestingly, the incidence of arrhythmias was enhanced in isolated atria from humans treated prior to surgery with β-adrenoceptor blockers [102,103]. The arrhythmias could be explained on a single cell basis via late afterdepolarizations [104,105]. In addition, arrhythmogenesis due to 5-HT might also involve stimulation L-type Ca…”
Section: Chronotropic and Proarrhythmic Effects Of 5-ht In The Heartmentioning
confidence: 95%